Periphyton nutrient content, biomass and algal community on artificial substrate: response to experimental nutrient enrichment and the effect of its interruption in a tropical reservoir - Santos, Suele Aparecida Mendes (2018)
Periphyton plays an important functional role in the retention of nutrients in aquatic ecosystems, especially phosphorus. We evaluated the effects of enrichment with N and P and the effect after 20 days of no additional N and P on periphyton on artificial substratum in open-bottom mesocosms. The aim was to jointly evaluate periphyton, phytoplankton and zooplankton in the presence of macrophytes. Experimental conditions simulated natural conditions and nutrient addition was based on the maximum concentration recorded in mesotrophic reservoir. Our hypothesis is that the periphyton is sensitive to the effects of N and P enrichment and its interruption, despite the positive response of phytoplankton and zooplankton. Two treatments were designed using open-bottom mesocosms (n = 3): control (no nutrient addition); NP+ (combined phosphorus and nitrogen addition). Sampling for the measurement of biotic and abiotic variables was performed, with 10 days of continuous enrichment, on the 3rd, 6th and 11th, and 20 days after enrichment had ended (31st day). Periphyton chlorophyll a, dry mass and algal density increased significantly with the addition of N and P and decreased 20 days after the interruption of the enrichment. The highest periphyton P content was found in the NP+ treatment. The enrichment had a positive effect on Chrysophyceae (Chromulina spp.) and rotifer (Polyarthra spp.) density and the interruption of enrichment favored Bacillariophyceae (Gomphonema sp.) and rotifers (Gastropus stylifer). Phytoplankton responded positively to enrichment. Along with the high macrophyte coverage over the experimental period, we evidenced the positive effect enrichment had on phytoplankton biomass and zooplankton abundance. Therefore, periphyton on artificial substrate was sensitive to effects of N and P enrichment and its interruption, responding promptly to changes in nutrient availability in a scenario of high competition and grazing.